Diseño de una arquitectura de sistemas de información para la administración del alineamiento a estándares académicos - Medina-Mora, Moises (Instituto Tecnológico de Costa Rica, 2018)
The main objective of this project is the design of an information system architecture for the curricular alignment to academic standards in secondary education institutions. The direct benefit for an educational institution when having this architectural design at its disposal is that it can be used as a framework for the development of information systems that will allow them to transform its traditional educational process into one that is a standard-based. Information systems enable the organizations to access the information in a fast, efficient, and inexpensive way, allowing the automation and improvement of their current processes. However, some information systems allow them to go further, providing the opportunity for a radical transformation, either by strategic decisions of the organization (voluntary), or because it is required by its environment (mandatory or regulatory). Likewise, an organization, or a whole group of organizations, eventually faces the challenges and demands that society imposes. In the specific case of the educational system and its institutions, a new generation of students highly influenced by the technology that surrounds them and provides them with an almost unlimited and immediate access to information has been one of the motivations to carry out a set of transformative changes to improve the quality of education in a society that is increasingly global and competitive. As a response to this, movements in education have emerged demanding the establishment of academic standards and key competences, like those used in the industry, to measure and improve quality in education, leading it to reach universal levels of competitiveness. This is the main motivation to develop the present project, and the result is a contribution to the transformation efforts from a traditional educational institution to one based on academic standards and competencies, through the design of an information systems architecture that can be used as a guide to develop information systems efficiently, consistently and with the appropriate quality attributes to maximize its use, performance, and longevity.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2018.
Keywords: Diseño; Arquitectura; Sistemas de Información; Estándares; Transformación